Prevalence of Perinatal Depression in Low- and Middle-Income Countries - Eunike, Eunike; Amalia, Amalia (International Medical Journal Corp. Ltd, 2024)
Background: The literature on perinatal depression in low- and middle-income countries (LMICs) underscores a significant public health concern characterized by high prevalence rates and detrimental consequences for both maternal and infant health. The studies reviewed collectively highlight the complex interplay of socio-economic, cultural, and health-related factors that contribute to the prevalence of perinatal depression in these contexts. Literature Review: The foundational work by Subba (2020) emphasizes the necessity of contextually adapted mental health promotion programs, demonstrating that maternal depression not only affects mothers but also poses risks to infant health, including increased susceptibility to illness and growth impairment. Furthermore, the study by Silva et al. (2021) sheds light on antenatal depression, revealing that depressive symptoms during pregnancy are alarmingly prevalent in LMICs and can lead to adverse outcomes for both mothers and infants. Lastly, the systematic review and meta-analysis by Rahman et al. (2021) consolidate evidence regarding the prevalence of perinatal depression in LMICs, revealing that it is a common morbidity with significant implications for maternal and infant health. Conclusion: In conclusion, the literature collectively emphasizes the pressing need for targeted interventions and contextually adapted mental health promotion programs to address the high prevalence of perinatal depression in LMICs. The identified socio-economic, cultural, and health-related determinants necessitate a nuanced approach to improve maternal and infant health outcomes in these vulnerable populations.